Comparative genomic analyses of Cutibacterium granulosum provide insights into genomic diversity - Chen, Peishan; Wang, Shaojing; Li, Hongyan; Qi, Xiaoye; Hou, Yuanyuan; Ma, Ting (Frontiers in Microbiology, 2024)
Cutibacterium granulosum, a commensal bacterium found on human skin, formerly known as Propionibacterium granulosum, rarely causes infections and is generally considered non-pathogenic. Recent research has revealed the transferability of the multidrug-resistant plasmid pTZC1 between C. granulosum and Cutibacterium acnes, the latter being an opportunistic pathogen in surgical site infections. However, there is a noticeable lack of research on the genome of C. granulosum, and the genetic landscape of this species remains largely uncharted. We investigated the genomic features and evolutionary structure of C. granulosum by analyzing a total of 30 Metagenome-Assembled Genomes (MAGs) and isolate genomes retrieved from public databases, as well as those generated in this study. A pan-genome of 6,077 genes was identified for C. granulosum. Remarkably, the 'cloud genes' constituted 62.38% of the pan-genome. Genes associated with mobilome: prophages, transposons [X], defense mechanisms [V] and replication, recombination and repair [L] were enriched in the cloud genome. Phylogenomic analysis revealed two distinct mono-clades, highlighting the genomic diversity of C. granulosum. The genomic diversity was further confirmed by the distribution of Average Nucleotide Identity (ANI) values. The functional profiles analysis of C. granulosum unveiled a wide range of potential Antibiotic Resistance Genes (ARGs) and virulence factors, suggesting its potential tolerance to various environmental challenges. Subtype I-E of the CRISPR-Cas system was the most abundant in these genomes, a feature also detected in C. acnes genomes. Given the widespread distribution of C. granulosum strains within skin microbiome, our findings make a substantial contribution to our broader understanding of the genetic diversity, which may open new avenues for investigating the mechanisms and treatment of conditions such as acne vulgaris.